2002
DOI: 10.1207/s15548430jlr3404_4
|View full text |Cite
|
Sign up to set email alerts
|

“Us Boys like to Read Football and Boy Stuff”: Reading Masculinities, Performing Boyhood

Abstract: Anthony, Ray, Lavell, Corey, Junius, and Kenneth jostled each other as they approached the front of the classroom. Several of their 5th grade classmates were already beginning to giggle as the boys assembled in a nervous knot facing their peers. Their teacher, Anna, shushed the class

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 17 publications
1
53
0
1
Order By: Relevance
“…Gender sociologists such as Chodorow (1978) and Kimmel (2006) have proposed related notions of constructed male identity in America, in that boys may attempt to build a masculine identity by rejecting anything that they perceive as feminine in nature. Empirically, support for this constructed masculinity having implications for literacy has been offered in the work of Dutro (2003) and Katz and Sokal (2003), in that both studies found participants to hold beliefs that reading was a feminine activity and should thus be rejected as gender inappropriate. Though not all boys or young men buy into the notion of hegemonic masculinity and strive to meet its demands, it is important to note that males in general do adhere more rigidly to gender expectations than females, although gifted students of both genders have traditionally rated high in psychological androgyny and may thus be more likely to read a wider selection of genres (Howard-Hamilton & Franks, 1995;Wilcove, 1998).…”
Section: Behaviors and Beliefsmentioning
confidence: 97%
See 1 more Smart Citation
“…Gender sociologists such as Chodorow (1978) and Kimmel (2006) have proposed related notions of constructed male identity in America, in that boys may attempt to build a masculine identity by rejecting anything that they perceive as feminine in nature. Empirically, support for this constructed masculinity having implications for literacy has been offered in the work of Dutro (2003) and Katz and Sokal (2003), in that both studies found participants to hold beliefs that reading was a feminine activity and should thus be rejected as gender inappropriate. Though not all boys or young men buy into the notion of hegemonic masculinity and strive to meet its demands, it is important to note that males in general do adhere more rigidly to gender expectations than females, although gifted students of both genders have traditionally rated high in psychological androgyny and may thus be more likely to read a wider selection of genres (Howard-Hamilton & Franks, 1995;Wilcove, 1998).…”
Section: Behaviors and Beliefsmentioning
confidence: 97%
“…Numerous gender researchers have rallied to explain these contrasts and their arguments have often been at odds. According to some, social perceptions of reading as a feminine activity have caused boys to flee from it (Dutro, 2003). Contrarily, Sax (2007a) argued that video games, television, attention deficit-hyperactivity disorder medications, and even endocrine disruptors from plastic have damaged boys' motivation and ability to concentrate.…”
Section: Males and Readingmentioning
confidence: 99%
“…Thus, "thinking of classroom literacy interactions as immutable essential characteristics of either males or females is problematic" (Moore, 1996, p. 18, cited in Evans, Alverman, & Anders, 1998. For example, research finds that the masculine performances of African American fifth grade boys are shaped by their reading choices and conversations about books (Dutro, 2003). Research also suggests that middle school girls' literacy and academic identities are influenced by the symbolic cultural capital girls gain when they abide by the prevailing expectations of femininity (Fairbanks & Ariail, 2006).…”
Section: Gender and Peer Workmentioning
confidence: 99%
“…As a result of this study, researchers began to focus not only on the textual content of these discussions, but on what else was happening in these groups. What first appeared as transactional, engaging, and democratic spaces for student discussion were now being analyzed for their complicated sociocultural influences (Cherland, 1994;Dutro, 2003;Evans, 1996aEvans, , 1996bEvans, , 2002Evans et al, 1998;Goatley, Brock, & Raphael, 1995;Hinchman & Peyton-Young, 2001; Lewis, 1998Lewis, , 2001.…”
Section: Literature Circles As Illustrative Casesmentioning
confidence: 99%